Bibliografía comentada. sobre historia oral e historia de vida - Jorge E. Aceves Lozano (Estudios sobre las Culturas Contemporáneas)
The author provides annotated information on 34 texts devoted to life history and oral history. This work is of great importance to historians and researchers in general, as the techniques mentioned are set up as relevant alternative research techniques and methods. Consultation sources are provided alongwith the text contents.